Empathy without Presence? Metacommunication, Language, and the Psychological Limits of Online Interaction - Németh, Erzsébet; Szoták, Szilvia; Dér, Dezső Cs. (Journal of Ecohumanism, 2026)
The increasing dominance of digitally mediated communication has fundamentally altered how individuals perceive, express, and respond to the emotions of others. This review paper examines how structural characteristics of online interaction influence the emergence and functioning of empathy, with particular attention to verbal expressiveness, metacommunication, feedback, and psychological consequences. Drawing on research from social psychology, cyberpsychology, communication studies, and sociolinguistics, the paper systematically compares offline, face-to-face communication with online, technology-mediated interaction.Online communication environments typically restrict spontaneous non-verbal cues, that play a crucial role in empathic understanding. Although users employ compensatory digital tools such as emojis, GIFs, abbreviations, and visual symbols, these consciously selected signals cannot fully replicate the automatic and embodied nature of metacommunication. As a result, emotional signals are more easily distorted, misunderstood, or overlooked, weakening mutual attention and empathic engagement.The paper also highlights the role of language in empathy development. Accelerated, fragmented, and reduced textual communication may limit nuanced emotional expression and negatively affect linguistic richness, particularly during early socialisation. This process may influence not only interpersonal understanding but also the development of inner speech, emotional self-reflection, and emotional regulation.Finally, the review discusses the broader psychological and social consequences of empathy deficits in online environments, including increased misunderstanding, dehumanisation, online disinhibition, cyberbullying, and social polarisation. The findings suggest that while digital platforms offer new forms of connection, they cannot fully replace the empathic depth enabled by embodied, synchronous, and multichannel human interaction. Understanding these limitations is essential for promoting healthier online communication and psychological well-being.